OpenWorm: an open-science approach to modeling Caenorhabditis elegans - Szigeti, Balázs; Gleeson, Padraig; Vella, Michael; Khayrulin, Sergey; Palyanov, Andrey; Hokanson, Jim; Currie, Michael; Cantarelli, Matteo; Idili, Giovanni; Larson, Stephen (Frontiers in Computational Neuroscience, 2014)
OpenWorm is an international collaboration with the aim of understanding how the behaviour of Caenorhabditis elegans (C. elegans) emerges through the underlying biophysical processes. The project has developed a modular simulation engine to create computational models of the worm. The modularity of the engine makes it possible to easily modify the model, incorporate new experimental data and test hypotheses. The modelling framework incorporates both biophysical neuronal simulations and a novel fluid-dynamics-based soft-tissue simulation for physical environment-body interactions. The project's open-science approach is aimed at overcoming the difficulties of integrative modelling within a traditional academic environment. In this article the rationale is presented for creating the OpenWorm collaboration, the tools and resources developed thus far are outlined and the unique challenges associated with the project are discussed.